Improvement of COD and color removal from UASB treated poultry manure wastewater using Fenton's oxidation - Yetilmezsoy, Kaan; Sakar, Suleyman (ELSEVIER, 2008)
The applicability of Fenton's oxidation as an advanced treatment for chemical oxygen demand (COD) and color removal from anaerobically treated poultry manure wastewater was investigated. The raw poultry manure wastewater, having a pH of 7.30 (+/-0.2) and a total COD of 12,100 (+/-910) mg/L was first treated in a 15.7 L of pilot-scale up-flow anaerobic sludge blanket (UASB) reactor. The UASB reactor was operated for 72 days at mesophilic conditions (32 +/- 2 degrees C) in a temperature-controlled environment with three different hydraulic retention times (HRT) of 15.7, 12 and 8.0 days, and with organic loading rates (OLR) between 0.650 and 1.783 kg COD/(m(3) day). Under 8.0 days of HRT, the UASB process showed a remarkable performance on total COD removal with a treatment efficiency of 90.7% at the day of 63. The anaerobically treated poultry manure wastewater was further treated by Fenton's oxidation process using Fe2+ and H2O2 solutions. Batch tests were conducted on the UASB effluent samples to determine the optimum operating conditions including initial pH, effects of H2O2 and Fe2+ dosages, and the ratio of H2O2/Fe2+. Preliminary tests conducted with the dosages of 100 mg Fe2+/L and 200 mg H2O2/L showed that optimal initial pH was 3.0 for both COD and color removal from the UASB effluent. On the basis of preliminary test results, effects of increasing dosages of Fe2+ and H2O2 were investigated. Under the condition of 400 mg Fe2+/L and 200 mg H2O2/L, removal efficiencies of residual COD and color were 88.7% and 80.9%, respectively. Under the subsequent condition of 100 mg Fe2+/L and 1200mg H2O2/L, 95% of residual COD and 95.7% of residual color were removed from the UASB effluent. Results of this experimental study obviously indicated that nearly 99.3% of COD of raw poultry manure wastewater could be effectively removed by a UASB process followed by Fenton's oxidation technology used as a post-treatment unit. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: poultry manure wastewater; Fenton's oxidation; pH; COD removal; ANAEROBIC-DIGESTION; TREATABILITY; COAGULATION; REACTOR; MODEL; Engineering; Environmental Sciences & Ecology